Draft Genome Sequence of Mycobacterium obuense Strain UC1, Isolated from Patient Sputum - Greninger, Alexander L. (Genome Announc, 2015)
We report the draft genome sequence of Mycobacterium obuense strain UC1 from a patient sputum sample. This is the first draft genome sequence of Mycobacterium obuense, a rapidly growing scotochromogenic mycobacterium.